Effects of milk cooling: A case study on milk supply chain for a factory in Ethiopia - Dijkink, Bert; Esveld, Erik; Broeze, Jan; Axmann, Heike; Vollebregt, Martijntje (2019)
Milk has important nutritious values and is therefore can contribute to nutrition security in Africa. The product category is a hotspot for food loss & waste and the associated greenhouse gas emissions in African countries. Therefore, adequate design of milk collection chains and choice of technology options is essential to make the food product available with minimum climate impact. In this study the effects of different scenarios for introducing a cold milk chain are evaluated based on rejection rates and costs to increase the milk supply of a milk factory near Solulta (Ethiopia). The effect of the scenarios on the milk is calculated with a model that combines temperature, growing rate, lactic-acid production to estimate the quality: chance of rejection on arrival at the factory. Introduction of chilling centres or on-farm cooling system can both make the evening milk delivery possible for the factory. For the first option, the implementation of a collection system will be critical, whereas for on-farm chilling the willingness to extend the power grid and the type of milk containers are essential. On-farm off-grid cooling systems seem not economically feasible in the studied area.